Beliefs and Attitudes towards Pakistan among Indian College students in relation to gender. - IRFAN, MOHAMMAD; Farooqi, Ramsha (IJRDO - Journal of Social Science and Humanities Research, 2021)
The objective of this study to Presence of a set of attitudes toward Pakistan, set of belief and attitudes may have favourable and unfavourable attitudes toward Pakistan among male and female Indian Punjabi students. The total sample of present investigation consisted of 80 Punjabi Indian students studying at Government College Malerkotla, Tara Vevek College Gangan Majra and Sample comprised of 40 males students and 40 females students. The results depicted that male and female students have same attitude and belief towards Pakistan. Further the results depicted that male and female students have favourable attitude and belief in “Sports’ and ‘Culture’ categories” towards Pakistan. There is no significant difference among the attitude and belief in Most favourable and favourable categories.